Lower Urinary Tract Symptoms in Prostate Cancer Patients Treated With Radiation Therapy: Past and Present - Kwon, Whi-An; Lee, Seo-Yeon; Jeong, Tae Yoong; Moon, Hong Sang (International neurourology journal, 2021)
The incidence of prostate cancer (PCa) is increasing concomitantly with population aging. Accordingly, interest in radiation therapy (RT) and the frequency of RT are also increasing. The types of RT can be broadly divided into external beam RT (EBRT), brachytherapy (BT), and combination therapy (EBRT+BT). Lower urinary tract symptoms (LUTS) after RT for the treatment of PCa are common; however, there are few reviews on the relationship between RT and LUTS. Herein, we review the causes and incidence of LUTS, as well as the evaluation and treatment options. Because of the reported risks of RT, patients undergoing RT should be counseled regarding the challenges of treatment and informed that they may have higher failure rates than nonirradiated patients. Moreover, thorough evaluation and treatment strategies are needed to support treatment recommendations. With a review of the existing literature, this narrative article provides an overview to aid urologists in treating patients presenting with complications associated with RT for the treatment of PCa. Further research is required to provide evidence of the effectiveness and feasibility of the management approach to the care of patients with LUTS after RT for the treatment of PCa.